SDGSAT-1 pendulum mirror coupling control technology - Xianghua Xie; Yingquan Yang; Yining Wang; Lingling Yan; Bihong Fu; Liang Chang (International Journal of Digital Earth)
Aiming at the on-orbit high-precision attitude control problem of coupling the periodic motion of the thermal infrared oscillating mirror of the Sustainable Development Scientific Goals Satellite-1 (SDG Satellite-1, SDGSAT-1) with the motion of the satellite, this paper designs an angular momentum feedforward compensation control method based on the motion information of the onboard motion mechanism and the measurement information of the onboard measurement component, and realizes the output of the integrated control moment through the Based on physical test on the air-bearing platform and on-orbit data of SDGSAT-1, the results show that the control method effectively compensates the disturbance moment caused by the motion mechanism, and the attitude control precision of the whole satellite system is high.onboard reaction wheels. Based on physical test on the air-bearing platform and on-orbit data of SDGSAT-1, the results show that the control method effectively compensates the disturbance moment caused by the motion mechanism, and the attitude control precision of the whole satellite system is high.